Ensaios sobre as exportações brasileiras de mamão - Nunes, Erivelton de Souza (2019)
Considering the nutritional and economic importance of the national papaya, this dissertation aims to analyze the Brazilian exports performance of this fruit, being composed of two chapters. The first is entitled “Spacial integration of export prices of brazilian papaya, considering transaction cost, during the period of 2001 to 2017”, proposed to analyse the spacial integrated process, considering the transaction cost, among Brazilian principal papaya exporting markets named as Espírito Santo, Rio Grande do Norte, Bahia e Paraíba. The methological procedures of Vector Correction Model (VEC) and Threshold Vector Correction Model (TVEC) were applied. The monthly price serie data of this commodity for the period of jannuary 2001 to december 2017 was used. The results indicate the existence of cointegration among these markets and also points out the presence of transaction cost in trasmission process of prices between Espírito Santo and Paraíba, also between Espírito Santo and Rio Grande do Norte. The second chapter is entitled "Determinants of Brazilian exports of papaya in light of the gravitational model", whose purpose was to analyze the determinants of Brazilian papaya exports, considering countries in Europe, South America and North America that represent almost 98 % of the total exports of this fruit from 2001 to 2016. For this purpose, the gravitational model was used, which consists of the application of the panel data methodology, and the per capita incomes of Brazil and the importing countries, distance, exchange rate, Index of Freedom of Business, international prices and binary variables that correspond to the economic block of which the importing country is a part, and the presence of the coast. The results showed that exports of Brazilian papaya are explained directly by the product of the economic sizes of Brazil and its commercial partners and inversely proportional to the distance that separates them. It is also worth mentioning the direct relationship between this trade flow and international prices, and the opposite with the exchange rate. In addition, the negative impacts of MERCOSUR and NAFTA on Brazilian papaya exports are also evidenced.